Adsorption of heavy metals by Lycium barbarum branch-based adsorbents: raw, fungal modification, and biochar. (24th February 2022) - Guan, Jian; Hu, Changwei; Zhou, Jun; Huang, Qingguo; Liu, Jiayang
Abstract: The present study reports on the adsorptive removal of heavy metals (Cr 3+, Cd 2+, and Cu 2+ ) from water by a series of Lycium barbarum branch-based adsorbents: Lycium barbarum branch (denoted as LB), fungal fermented LB (FLB), LB biochar (LBB), FLB biochar (FLBB), alkaline modified LBB (ALBB), and alkaline modified FLBB (AFLBB). The six adsorbents were characterized in terms of FTIR, SEM, surface area and pore size as well as zeta potential. The adsorptive potential of these adsorbents was tested under varying conditions – pH, contact time, initial concentration, and temperature. Adsorption results were well fitted with Langmuir, Freundlich, and Temkin models. The maximum adsorption capacity ( q m ) was calculated to be 6.29 mg/g for Cr 3+ by FLB, 11.53 mg/g for Cd 2+ by LB, and 7.27 mg/g for Cu 2+ by LB. The pseudo-second-order kinetic equation better described the adsorption process. Based on the thermodynamics parameters, the adsorption of heavy metals was endothermic but not spontaneous for biochars. The experimental results offer a new way for recycling and reutilizing LB in wastewater treatment. HIGHLIGHTS: Lycium barbarum branch (LB) was used to adsorb Cu 2+, Cr 3+, and Cd 2+ . LB was further modified with fungal fermentation and O2 -free pyrolysis. Isotherm, kinetic, and thermodynamic of adsorption were fitted and analyzed. Modified LB-based adsorbents showed varied adsorption capacity and behavior. LB and FLB are novel and promising adsorbents. Graphical Abstract